PENGARUH DISIPLIN, MOTIVASI KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN YAYASAN PENGEMBANGAN PENDIDIKAN DINAMIKA (YPPD) CIKARANG - Saga Cindai Alisanda; Tjiptogoro Dinarjo Soehari (Akademika, 2019)
This study aims to get information about the influence of discipline, work motivation and compensation to employee performance of development Foundation dynamics Cikarang. This study using quantitative approach conducted in five levels of schools; nursery school, elementary school, junior high school, vocational school and college under Development Foundation Dynamics Cikarang. This study conducted by using the method of the survey with analysis lines in the hypothesis testing. In this study sample size of saturated is 101. research focused on three aspects; discipline, motivation and compensation in the Development FoundationEducation Dynamics Cikarang. The data collected by the questionnaires and analyzed with analysis path. The results of the analysis concluded that (1) there is a direct influence positive discipline to employee performance Ckarang. (2) there is a direct influence positive motivation to employee performance Cikarang, and (3) there is a direct influence positive compensation to employee performance Cikarang